PERBAIKAN TANAH MENGGUNAKAN METODE PRELOADING KOMBINASI PVD PROYEK AKATARA GAS PLANT FACILITY - Wicaksono, Luthfi Amri; Tasya Afkarina; Paksitya Purnama Putra (Jurnal Teknik Sipil, 2024)
Soft soil is a serious problem in the implementation of the Akatara Gas Plant Facility Project because soft soil has a low bearing capacity and experiences large settlements. Effective soil improvement to solve this problem is PVD combination preloading methods. This research aims to plan soil improvement for the primary road construction of the Akatara Gas Plant Facility project in Jambi using PVD combination preloading method. The planned PVD is non-woven PVD with variations in size: 9.5 cm wide, 3.5 cm thick, 10 cm wide, 0.4 cm thick, and 10.5 cm wide, 4.5 cm thick. Calculation of consolidation time after PVD was carried out using triangle and square patterns with varying distances of 100 cm, 110 cm, 130 cm and 150 cm. Based on the analysis results, soil preloading could not be applied because it collapsed, so soil preloading was combined with vacuum preloading. The vacuum preloading used has a capacity of 80 kPa and the required embankment is 3.93 meters high. The planned PVD depth is 12 meters deep. 90% consolidation time required at a distance of 100 cm triangle pattern, 100 cm square pattern, 110 cm triangle pattern, 110 cm square pattern, 130 cm triangle pattern, 130 cm square pattern, 150 cm triangle pattern and 150 cm square pattern cages are 13 weeks, 15 weeks, 9 weeks, 10.5 weeks, 13 weeks, 15.5 weeks, 18 weeks, and 21 weeks. The most effective PVD installation distance and pattern is a distance of 110 cm with a square pattern. The choice of distance and installation pattern is adjusted to the work time for soil improvements on the Akatara Gas Plant Facility Project.